Qualitative Analysis of Character Education Through Congregational Prayer at the Raudlatul Muta'allimin Cilendek Islamic Boarding School, Tasikmalaya City - Yanto Maulana Restu; Miswan Ramdani; Dodo Murtado; Bambang Samsul Arifin; Aan Hasanah (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to investigate the application of character education through the implementation of congregational prayers at the Raudlatul Muta'allimin Cilendek Islamic Boarding School, Tasikmalaya City. Qualitative research methods were used to examine this research. The data sources in this research include observations, documentation, interviews and are equipped with primary data sources and secondary data sources from various trusted references such as scientific journals, books and other sources that support the research. Data analysis in this study includes steps such as data collection, data presentation, data reduction, and deduction of conclusions. The results of the study show that congregational prayer not only strengthens religious values, but is also a means of forming good character for students, among others. Among the character values instilled in Raudlatul Muta'allimin Cilendek Islamic boarding school students are: obedience (ta'at), discipline, humility (tawadhu'), brotherhood (ukhuwah), patience (sabr), example (uswah), self-control (mujahadah), commitment and consistency.